Permanent plot for monitoring in a galleria forest in Puerto Gaitan Meta - Gutiérrez, Albert; García, Fernando; Rojas, Salvador; Castro, Francisco (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
In 2010, Corpoica began in the dissected eastern plains of Colombia, the installation and study of the structure and floristic composition in a permanent one-hectare plot located in the tropical bioclimatic unit called gallery forest, in the municipality of Puerto Gaitan, Meta. The plot was laid out and demarcated; then, were identified and measured all individuals with DBH greater than ten centimeters. Accordingly with floristic composition were founded 519 individuals belonging to 72 species, 56 genera and 36 families of woody plants were recorded. Families with highest species richness were Burseraceae (5), Euphorbiaceae (5) and Clusiaceae (5). The main uses of the 72 species were 32 timber, 18 wildlife feeding, 10 watersheds protective nature, five suppliers of wood, three fruits, one dye production and one ornamental. The highest tree recorded for the parcel height was 21 meters reported by individuals in the “chaparro de agua” Panopsis rubescens and “merecurillo blanco” (Licania kunthiana). The species “tuno” (Miconia sp) and “quincedias” (Tapirira guianensis),were the two species with higher importance value index (IVI) 29.5% and 23.8%, respectively. In the vertical and horizontal structure analysis was observed that the middle stratum (Em) showed a 46.9% coverage, corresponding to a basal area (6.87 m2), the top stratum (Es) 45.7% (6.69 m2) and the lower stratum (Ei) 7.41% (1.09 m2). The results suggest that these areas are diverse both in structure and floristic composition and this diversity are affected by human disturbance as there is presence of clear effect of selective logging.